2017
DOI: 10.1108/bpmj-10-2016-0211
|View full text |Cite
|
Sign up to set email alerts
|

Open innovation in specialized SMEs: the case of supercars

Abstract: Purpose: The purpose of this paper is to explore the influence that adopting open innovation (OI) has on the innovativeness and performance of specialized small and medium-sized enterprises (SMEs). This paper also examines the adoption of OI within a firmâ\u80\u99s practices and models, and within the three dimensions of firm sustainability. Design/methodology/approach: Survey data from 48 specialized SMEs manufacturing supercars were analyzed using partial least squares structural equation modeling. SmartPLS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 126 publications
(305 reference statements)
2
29
0
Order By: Relevance
“…An examination of the SME and internationalization literature in the missing aspects of barriers of SMEs' internationalization produced results demonstrating a slightly significant weighting of political issues over socioeconomic barriers. Previous studies such as Ardito, D'Adda, and Petruzzelli () and (Ramirez‐Portilla, Cagno & Brown, ) missed this earlier. We have extended (Brennan & Jaworski, ) two‐phased inward/outward model by providing further insights into three key barriers (political, economic, and social) that impact on the survival of SMEs, whereas Paul and Anantharaman () focused on some people management practices globally (Liñán et al, ).…”
Section: Discussionmentioning
confidence: 86%
“…An examination of the SME and internationalization literature in the missing aspects of barriers of SMEs' internationalization produced results demonstrating a slightly significant weighting of political issues over socioeconomic barriers. Previous studies such as Ardito, D'Adda, and Petruzzelli () and (Ramirez‐Portilla, Cagno & Brown, ) missed this earlier. We have extended (Brennan & Jaworski, ) two‐phased inward/outward model by providing further insights into three key barriers (political, economic, and social) that impact on the survival of SMEs, whereas Paul and Anantharaman () focused on some people management practices globally (Liñán et al, ).…”
Section: Discussionmentioning
confidence: 86%
“…Presenza et al (2016) highlight in regard to lowtechnology SMEs, that OI activities increase the firm's ability to innovate and that customers are regarded as the most important external source for innovation. Besides increasing innovativeness, Ramirez-Portilla et al (2017) demonstrate that adopting OI practices further supports SMEs to become more sustainable and resource-efficient and increases their overall competitiveness. Furthermore, Kim and Park (2010) found that adopting external R&D corporations has a positive significant impact on SME's innovation output, whereas external ideas have a negative impact and external knowledge has no impact.…”
Section: Smes' Innovation Performance and Outputmentioning
confidence: 97%
“…Ramirez-Portilla et al 98 analyse data from 48 specialised SMEs involved in manufacturing supercars. They affirm that the adoption of OI models and practices tends to increase firm innovativeness and improve the performance of SMEs.…”
Section: Overview Of the Analysed Trendsmentioning
confidence: 99%